Research on UAV UWB/IMU Tight Integrated Navigation and Positioning Algorithm - HUANG Junbo; LUO Zhexuan; LI Junpeng; JIN Tao; YU Zhilong (Journal of Harbin University of Science and Technology, 2024)
Navigation and positioning technology is the core technology for UAV to perform tasks stably. In this paper, the tight integrated navigation algorithm of Inertial Navigation System (INS) and Ultra Wide Band (UWB) is studied to meet the needs of UAV indoor navigation and positioning. Firstly, the strapdown inertial navigation system and UWB positioning system are modeled. Then, the loose combination and tight combination of UWB and INS are designed to fuse the information of UWB and INS, restrain the drift error of INS, and reduce the impact of non line of sight environment and communication interruption on the accuracy of UWB positioning system. The state equation and observation equation of UWB/IMU loose and tight integrated navigation algorithm are designed. Finally, a simulation experiment is designed to compare the tight combination with loose combination of UWB and INS. The simulation experiment proves that the tight combination of UWB with INS has higher precision and stronger anti-interference ability than the loose combination.